African primary care research: Performing surveys using questionnaires - Indiran Govender; Langalibalele H. Mabuza; Gboyega A. Ogunbanjo; Bob Mash (AOSIS, 2014)
The aim of this article is to provide practical guidance on conducting surveys and the use of questionnaires for postgraduate students at a Masters level who are undertaking primary care research. The article is intended to assist with writing the methods section of the research proposal and thinking through the relevant issues that apply to sample size calculation, sampling strategy, design of a questionnaire and administration of a questionnaire. The articleis part of a larger series on primary care research, with other articles in the series focusing on the structure of the research proposal and the literature review, as well as quantitative data analysis.